Smooth conversations: sexuality as a linguistic resource in a secondary language classroom. Issue 1 (2nd January 2020) - Simonsson, Angelica
ABSTRACT: In the present article, the interlinking between language and sexuality in a secondary language classroom is explored. The aim of the article is to examine use of performances of sexuality in conversation practices in an English classroom in a Swedish secondary school. The data production method is classroom observations, and the examples analysed are taken from field notes made during three grade eight English lectures in a Swedish secondary school. Using concepts of normativity and performativity, I analyse how sexuality is employed in classroom conversations. The results show that reproduction of heteronormativity seems intrinsic to language education in these cases. The pupils, in various ways, employ sexuality as a common bond that facilitates smooth conversations, for instance by using references to hypothetical heterosexual relationships, thereby positioning themselves as heterosexual, or by drawing on other recognizable performances of, e.g. femininity, masculinity and heterosexuality.